Meckel’s diverticulum and its plethoric presentation in paediatric surgery: a case series - Rajaram, Gomalaadevee; Singh, Pavin Kaur Bal Baldev; Madzlan, Muhammad Firdaus Bin; Fernandez, John Emmanuel Gilbert; Badarudin, Nurdaliza Binti Mohd (International Surgery Journal, 2021)
Meckel’s diverticulum (MD) is a congenital abnormality of the gastrointestinal tract resulting from incomplete obliteration of the vitellointestinal duct by 5th to 7th week of gestation. Incidence is 2% in the general population with a 2:1 male to female ratio. The various presentations of MD include gastrointestinal bleeding, intestinal obstruction, diverticulitis and intestinal perforation. Majority of the MD is asymptomatic however the potential risk of developing complication it's about 4-6%. Preoperative diagnosis of MD is challenging. We present 6 cases of MD managed at our centre over the course of 1 year. Two cases presented as intestinal obstruction secondary to mesodiverticular band from MD, one case with bleeding, two cases with intussusception and one case of meckel’s diverticulitis.